SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DESTINASI WISATA DI KOTA PANGKAL PINANG MENGGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY - Blenski, Andre; Hugeng; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Pangkal Pinang City is one of the City Government Areas in Indonesia is a member of the Bangka Belitung Islands Province Is also the capital of the province. Pangkalpinang City is divided into 7 districts namely Taman Sari, Rangkui, Pangkal balam, Gabek, Bukit Intan, Girimaya and Gerunggang. There are many local tourist destinations in The city of Pangkal Pinang, some of which are Pukan Beach, Bangka Botanical Garden, Pangkal Pinang Bangka Golden Bridge, Merdeka Park Square, and etc. The purpose of this research is to advance tourism in areca nut. In this study using the Multi Attribute Utility method theory. This method was chosen because it helps to determine the number of destination tours, distance and travel time to tourist destinations, tourist ticket prices, facilities and infrastructure, cleanliness and security of tourist destinations in the base city betel nut. Results From this study, the results obtained are knowing the distance and the time taken, the number and types of tours in Pangkal Pinang, level of cleanliness and security as well as ticket prices for each tourist destination in the city of Pangkal Pinang.